Simultaneously determination of fine particle dose of vilanterol and fluticasone furoate for dry powder inhaler (DPI) by utilizing gradient elution in chromatography system - Ewelina Szalek; Boguslawa Musial; Kamila Czarnecka; Paweł Szymański (Polskie Towarzystwo Farmaceutyczne, 2023)
Vilanterol (VT) and fluticasone furoate (FF) are components recently used in dry powder inhaler (DPI) to be administrated for patients with respiratory diseases, such as asthma or chronic obstructive pulmonary disease (COPD). In the present study, an approach to an analytical procedure development and validation is presented. Next generation impactor (NGI) and high performance liquid chromatography (HPLC) with UV detector were applied to determine two compounds and fine particle dose (FPD) of each active ingredients in DPI. The most satisfying chromatographic separation was obtained on Poroshell SB C18 (100 mm × 4.6 mm, 2.7 µm) column applying gradient elution by phosphonate buffer and acetonitrile. VT and FF were detected on a UV detector at wavelength of 210 nm and 245 nm, respectively. Among various coating agents, 4% polyethylene glycol PEG 200 in acetone (w/v) was selected as the most effective. Although various physicochemical properties of VT and FF, the analytical procedure allows simultaneously determine two compounds at different wavelengths. Limit of quantitative (LOQ) of vilanterol and fluticasone furoate were determined as 0.049 µg/ml and 0.032 µg/ml, respectively, what is desirable to determine of FPD of active ingredients in microdoses in DPI. The analytical procedure was determined as linear and accurate in the range of LOQ - 2.5 µg/ml and LOQ - 10.0 µg/ml of VT and FF, respectively. The coefficient of determination (R2) was found to be 0.9999 and 1.000 for VT and FF, respectively.